Metal‐Free Perovskite Piezoelectric Nanogenerators for Human–Machine Interfaces and Self‐Powered Electrical Stimulation Applications. Issue 18 (20th April 2022) - Wu, Han‐Song; Wei, Shih‐Min; Chen, Shuo‐Wen; Pan, Han‐Chi; Pan, Wei‐Pang; Huang, Shih‐Min; Tsai, Meng‐Lin; Yang, Po‐Kang
Abstract: Single crystal metal‐free halide perovskites have received great attention in recent years owing to their excellent piezoelectric and ferroelectric properties. However, the nanotoxicity and piezoelectricity within the nanoscale of such materials have yet been reported for the demonstration of practical applications. In this work, the observation of intrinsic piezoelectricity in metal‐free perovskite (MDABCO‐NH4 I3 ) films using piezoresponse force microscopy (PFM) is reported. A cytotoxicity test is also performed on MDABCO‐NH4 I3 to evaluate its low‐toxic nature. The as‐synthesized MDABCO‐NH4 I3 is further integrated into a piezoelectric nanogenerator (PENG). The MDABCO‐NH4 I3 ‐based PENG (MN‐PENG) exhibits optimal output voltage and current of 15.9 V and 54.5 nA, respectively. In addition, the MN‐PENG can serve as a self‐powered strain sensor for human–machine interface applications or be adopted in in vitro electrical stimulation devices. This work demonstrates a path of perovskite‐based PENG with high performance, low toxicity, and multifunctionality for future advanced wearable sensors and portable therapeutic systems. Abstract : Here, the integration of metal‐free perovskite MDABCO‐NH4 I3 into a piezoelectric nanogenerator (MN‐PENG) device is demonstrated. The high‐performance, low‐toxic, and flexible MN‐PENG device shows great potential in biomechanical energy harvesting, human–machine interfaces, and electrical stimulation therapy applications.